An incongruence-based anomaly detection strategy for analyzing water pollution in images from remote sensing - Dias, Maurcio Arajo [UNESP]; da Silva, Erivaldo Antnio [UNESP]; de Azevedo, Samara Calado; Casaca, Wallace [UNESP]; Statella, Thiago; Negri, Rogrio Galante [UNESP] (MDPI, 2020)
The potential applications of computational tools, such as anomaly detection and incongruence, for analyzing data attract much attention from the scientific research community. However, there remains a need for more studies to determinehowanomaly detection and incongruence applied to analyze data of static images from remote sensing will assist in detecting water pollution. In this study, an incongruence-based anomaly detection strategy for analyzing water pollution in images from remote sensing is presented. Our strategy semi-automatically detects occurrences of one type of anomaly based on the divergence between two image classifications (contextual and non-contextual). The results indicate that our strategy accurately analyzes the majority of images. Incongruence as a strategy for detecting anomalies in real-application (non-synthetic) data found in images from remote sensing is relevant for recognizing crude oil close to open water bodies or water pollution caused by the presence of brown mud in large rivers. It can also assist surveillance systems by detecting environmental disasters or performing mappings.
Keywords: Analysis of images pattern recognition; Anomaly detection; Classification; Incongruence; Remote sensing